2021
DOI: 10.2217/pgs-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Discordant CYP2D6 Genotyping Results in Thai Subjects: Platform Limitations and Novel Haplotypes

Abstract: Aim: Several CYP2D6 Luminex xTAG genotype calls were identified as inconsistent or suspicious among Thai subjects and further characterized to identify the root causes. Material & methods: Forty-eight subjects were followed-up with long-range-PCR, quantitative copy number assays and/or Sanger sequencing. Results: Most of the Luminex-duplication calls were either negative or had hybrid structures involving CYP2D6*36 in various configurations. Ten samples were inaccurately called as CYP2D6*2, *29 or *35 alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This, however, can be problematic, as rare population-specific variants may not be adequately identified. As a result, a patient’s predicted CYP2D6 metabolizer status, which is typically used for drug and/or dosing recommendations, may not be accurate [ 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, however, can be problematic, as rare population-specific variants may not be adequately identified. As a result, a patient’s predicted CYP2D6 metabolizer status, which is typically used for drug and/or dosing recommendations, may not be accurate [ 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…From this sample set (n = 211), 96 samples were randomly selected and subjected to Illumina high-throughput sequencing. First, XL-PCR amplicons (6.7 kb) were generated with a CYP2D6 -specific forward (5′-TCACCCCCAGCGGACTTATCAACC-3′) and reverse (5′-CGACTGAGCCCTGGGAGGTAGGTAG-3′) primer set [ 46 , 47 ]. This XL-PCR amplicon is referred to here, and in previous publications, as Fragment A. XL-PCR products were sheared on a Covaris ® instrument to an estimated size of 300 bp.…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested that the CYP2D6*10 frequency was overestimated in the past because the available platforms were unable to detect structural variants. Luminex, MassArray, and TaqMan platforms cannot detect the CYP2D6-2D7 hybrid of *36 , leading to an erroneous assignment of CYP2D*36+*10 as *10 [ 34 , 54 ]. In the current study, we performed long-range PCR with a *36 -specific primer set described by Soyama et al .…”
Section: Discussionmentioning
confidence: 99%
“…Samples with CNVs detected by XL-PCR were subjected to droplet digital PCR (ddPCR) to quantitatively measure copy number. ddPCR was performed as previously described [ 27 , 31 ] using TaqMan™-based copy number assays (Thermo Fischer, Waltham, MA, USA) with the following modification and published by Wen et al [ 32 ]: intron 6 copy number was interrogated as a single assay and copy number of the 5′UTR, and exon 9 targets were duplexed in an amplitude-based single reaction. Droplets were generated, thermal cycled, and read using the Bio-Rad QX200 AutoDG Droplet Digital PCR System (Bio-Rad Laboratories, Hercules, CA, USA) per manufacturer protocol.…”
Section: Methodsmentioning
confidence: 99%